Le personnage houellebecquien dans le monde décadent - Modrzejewska, Krystyna (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
Michel Houellebecq in his novels Platform (2001), Map and territory (2010) andSubmission (2015) shows the struggles of a man trying to find his place in the modern world.Author’s alter egos – writer, painter, clerk of the Ministry of Culture, researcher in literarystudies, witness a deep crisis that heralds the end of Europe. Unbridled consumption,clumsy journalists, crisis of democracy and Church’s institution are leading to the collapseof the old world. The prospect of being absorbed by Muslims, led by an extremely skilledpolitician, confirms Houellebecq’s talent, arousing anxiety and opposition.